Results of a Screening for von Willebrand Disease Type 2N in Patients with Suspected Haemophilia A or von Willebrand Disease Type 1 - Schneppenheim, Reinhard; Budde, Ulrich; Krey, Sonja; Drewke, Elke; Bergmann, Frauke; Lechler, Eberhard; Oldenburg, Johannes; Schwaab, Rainer (Thrombosis and Haemostasis, 1996)
A screening program for the detection of patients with von Willebrand disease type 2N (VWD 2N) was carried out in 177 unrelated patients previously diagnosed with haemophilia A and in 199 unrelated patients with VWD type 1 in comparison. By measuring the factor VIII (FVIII) binding capacity of von Willebrand factor (VWF), we detected 13 patients with VWD 2N within 8 unrelated families. The former diagnosis has been haemophilia A in 5 index patients, and VWD in the remaining 3. Included in this study were 14 patients with suspected haemophilia A, whose molecular analysis for mutations in the FVIII gene was unsuccessful. Five of them had VWD 2N. In all patients with the VWD 2N phenotype we were able to identify specific molecular defects in the corresponding DNA sequence of the FVIII binding domain of VWF. The most common defect was R91Q. Four patients from 4 families were homozygous for R91Q, six patients from 3 families were compound heterozygous for R91Q and a silent yet unidentified allele. The VWD 2N phenotype of father, daughter, and son in one family, was based on 2 different genotypes, compound heterozygosity for R91Q and VWD type 1 in the father and the daughter, and homozygosity for R91Q in the son. Two patients from one family were compound heterozygous for T28M and ΔC2680-2685 in exon 18, and one patient was compound heterozygous for a novel candidate missense mutation in exon 18 (E24K) and ΔC2680-2685 in exon 18 which is regarded the most common defect causing severe VWD type 3. FVIII:C values of 0.07 and 0.14 IU/ml were observed in patients with the genotype T28MIΔC2680-2685 whereas in patients being homozygous or compound heterozygous for R91Q, FVIII:C was 0.19 ° 0.071 IU/ml. In contrast to the other genotypes, E24KIΔC2680-2685 is correlated with a more severe haemophilic phenotype with a FVIII residual activity of only 0.01-0.02 IU/ml. This emphasizes the need for inclusion of the factor VIII binding assay in the diagnostic workup of suspected haemophilia A.